‘I did my bit’: terrorism, tarde and the vehicle ramming attack as an imitative event - Miller, Vincent (The British journal of criminology, 2019)
This paper considers the recent phenomenon of the vehicle-ramming attack (VRA): i.e. the act of purposely driving a vehicle into pedestrians and populated vehicles. It documents the recent (2015–2017) rise in the prevalence of ramming attacks and how these incidents challenge some of the assumptions we have about terrorism and its causes. Typically, criminologists and terrorist scholars tend to focus on either the ‘psychology’ of individual terrorists or wider structural or ethno-political issues, such as religion, ideological doctrine or the role of terrorist organizations in converting and recruiting people to violence. This paper will adopt a different position, one which focusses less on structure and individual psychology, and more on the act itself, as something that is not merely an expression of an individual or an ideology, but something that has a lure and force all of its own, as something that travels through our contemporary mediascape, to be internalized and imitated by an increasingly varied set of subjects with varying motivations, psychologies, ideologies and circumstantial backgrounds.